2020
DOI: 10.1371/journal.pone.0229927
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic disturbance regimes alter patterns of ecosystem variability and recovery

Abstract: Altered ecosystem variability is an important ecological response to disturbance yet understanding of how various attributes of disturbance regimes affect ecosystem variability is limited. To improve the framework for understanding the disturbance regime attributes that affect ecosystem variability, we examine how the introduction of stochasticity to disturbance parameters (frequency, severity and extent) alters simulated recovery when compared to deterministic outcomes from a spatially explicit simulation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(98 reference statements)
0
8
0
Order By: Relevance
“…Given the well‐documented role of burn severity in altering competitive dynamics between coniferous and deciduous species in the North American boreal (Johnstone and Chapin 2006, Whitman et al 2018), this variation between topographic position indicates that black spruce may retain competitive advantage longer in lowlands under single fires or reburn events. However, lowland plots still underwent a transition to deciduous communities linked with a removal of organic layers, indicating potential resilience via initially lower soil consumption (implying lower fire intensity) is limited and that, as predicted by theory, frequency of events is as important as any disturbance characteristic in driving recovery trajectories (Fraterrigo et al 2020).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Given the well‐documented role of burn severity in altering competitive dynamics between coniferous and deciduous species in the North American boreal (Johnstone and Chapin 2006, Whitman et al 2018), this variation between topographic position indicates that black spruce may retain competitive advantage longer in lowlands under single fires or reburn events. However, lowland plots still underwent a transition to deciduous communities linked with a removal of organic layers, indicating potential resilience via initially lower soil consumption (implying lower fire intensity) is limited and that, as predicted by theory, frequency of events is as important as any disturbance characteristic in driving recovery trajectories (Fraterrigo et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…Long-term shifts to different disturbance regimes (e.g., higher frequency) or other feedbacks can allow new community types to persist, driving fundamental shifts in ecosystem structure (e.g., grazing and fires, Archibald et al 2005; coral reef functioning, Jones et al 2004). Theoretical modeling agrees and further suggests changes in disturbance frequency are more important than changes to severity or other disturbance characteristics (Fraterrigo et al 2020) in driving variability in recovery.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, we could explore how a progressive increase in pulse intensity might affect the capacity of the system to recover between individual pulses and compare this to ecosystem recovery over a prolonged period without direct manipulation. Indeed, variation in the nature of ecosystem disturbance (e.g., frequency and intensity of pulses, duration and timing of disturbance) can have important consequences for ecosystem variability in general (Fraterrigo et al 2020), and for recovery dynamics in particular (Zelnik et al 2018). Across the entire study, we found that the strong non‐additivity of ecosystem responses to our nutrient manipulations were remarkably similar in both years.…”
Section: Introductionmentioning
confidence: 99%
“…The understory vegetation developmental process in a young tree stand at the stem exclusion stage can be generally explained, whereas little is known regarding the changes in this process over midor long-term observational periods (Halpern & Lutz, 2013). Efforts are underway to understand the relative importance of heterogeneous processes that change in line with the successional processes in an ecosystem (Chase & Myers, 2011;Fraterrigo et al, 2020;Liu et al, 2018;Royo & Ristau, 2013).…”
Section: Introductionmentioning
confidence: 99%